The Improvised Design of Headphone using Integrated Kano and Importance-Performance Analysis for Enhancing Customer Satisfaction - Akmal, S.; Hashim, N.; Norizan, A.; Yahaya, S. H. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Customer satisfaction is the best indicator for designers to stay competitive in today’s global market. Traditionally, survey was commonly used by designers to elicit customer satisfaction. However, survey has a limitation on identifying the design attributes that can increase customer satisfaction. Therefore, to overcome that limitation, this study proposed Kano model which was integrated into Importance-Performance Analysis (IPA) method through the calculation of customer satisfaction and customer dissatisfaction index. Kano-based questionnaires on headphone design were distributed to 400 respondents of young generations. The results of integrated approach interestingly showed that the design attributes that are related to technology such as Wi-Fi USB connector of headphone are perceived as important attributes and could effectively enhance the young generation satisfaction.